Perfil clínico e epidemiológico de pacientes portadores de fenilcetonúria no estado de Goiás - Figueira, Vandressa Barbosa (2018)
Phenylketonuria is a genetic disorder of an autosomal recessive nature, caused by the deficiency or absence of the enzyme phenylalanine hydroxylase. This enzyme is responsible for the conversion of phenylalanine to tyrosine and its substrates. From the absence of these products, the individual starts to present cognitive deficits that can reach irreversible sequels. The taste and limitation of foods allowed in patient feeding is a major obstacle in adherence to treatment. There are many types of formulas present in the market and, in addition, protein substitutes are offered in capsules, bars and sachets with taste and smell of fruit, for better acceptance. Adequacy and regular follow-up of the diet are essential points for prevention of adverse effects. In this way, the team must provide guidance to the family to know the importance of nutritional therapy, which must be carried out throughout life. This study aimed to analyze the profile of patients with phenylketonuria followed by the Reference Service in Neonatal Screening in the State of Goiás. A cross - sectional study was conducted with a quantitative approach and a documental basis. The medical records of the patients with phenylketonuria were used, accompanied by the referral service in neonatal screening in the State of Goiás. Sociodemographic, obstetric, diagnostic and consultative data were collected from the collection. The sample consisted of 78 patients in outpatient follow-up at the referral service. In the educational variable of the mother, there was a statistically significant association with incomplete primary education (p = 0.019) and occurrence of complication. There was also a significant association in the variable of schooling of the father, related to incomplete primary education (p = 0.002). There were associations between complications, late diagnosis and dietary neglect. It is possible to notice that with adequate follow-up, the blood levels of phenylalanine can be controlled, guaranteeing a good prognosis to the patient. Adherence to dietary treatment provides an excellent quality of life for the patient with phenylketonuria and can significantly reduce the risks of complications and sequelae. Family support and the particular attention of the multiprofessional team are essential facilitators for successful follow-up. Thus, we can corroborate that the disease does not become an obstacle for the social and economic inclusion of individuals. To conclude, we emphasize the importance of the multiprofessional team in the follow-up of these patients, and the importance of the family structure in this process, s